Technical aspects of using human adenovirus as a viral water quality indicator. (1st June 2016) - Rames, Emily; Roiko, Anne; Stratton, Helen; Macdonald, Joanne
Abstract: Despite dramatic improvements in water treatment technologies in developed countries, waterborne viruses are still associated with many of cases of illness each year. These illnesses include gastroenteritis, meningitis, encephalitis, and respiratory infections. Importantly, outbreaks of viral disease from waters deemed compliant from bacterial indicator testing still occur, which highlights the need to monitor the virological quality of water. Human adenoviruses are often used as a viral indicator of water quality (faecal contamination), as this pathogen has high UV-resistance and is prevalent in untreated domestic wastewater all year round, unlike enteroviruses and noroviruses that are often only detected in certain seasons. Standard methods for recovering and measuring adenovirus numbers in water are lacking, and there are many variations in published methods. Since viral numbers are likely under-estimated when optimal methods are not used, a comprehensive review of these methods is both timely and important. This review critically evaluates how estimates of adenovirus numbers in water are impacted by technical manipulations, such as during adenovirus concentration and detection (including culturing and polymerase-chain reaction). An understanding of the implications of these issues is fundamental to obtaining reliable estimation of adenovirus numbers in water. Reliable estimation of HAdV numbers is critical to enable improved monitoring of the efficacy of water treatment processes, accurate quantitative microbial risk assessment, and to ensure microbiological safety of water. Graphical abstract: Highlights: Concentration and detection methods for human adenovirus (HAdV) are evaluated. Methods chosen affect the accuracy of enumerating HAdV in water. HAdV culture analyses using non-permissive lines are underestimating numbers. HAdV qPCR performs favourably for water quality monitoring and risk assessment. Quantitative PCR provides capacity for early notification of water contamination.